Islands Landwirtschaft.: Grundzüge und neuere Wandlungen - Taubmann, Wolfgang (ERDKUNDE, 1969)
The structural basis of Icelandic agriculture is formed by a pastoral economy, determined by the cold boundary. Altitudinal limits as the inner boundary and the coast as the outer boundary restrict the potential agricultural area. Soil erosion poses a permanent danger. Within this natural framework there have been deep reaching changes since the turn of the century. At the beginning of the 20th century, Iceland was still without real urban centres and the overwhelming part of the population was dependent on agriculture and fishing. Against the background of increasingly favourable climate population and economic growth occurred, giving impulse to a spatial and social transformation of the population, shifts in the settlement limit and a State policy of expansion. Emerging markets caused differentiation in farm structure and spatial patterns in what had previously been undifferentiated agriculture. The cultivated meadows in close proximity to the farmstead (tun), whose area has increased sixfold since 1900, have been of decisive importance in the system of agricultural land. Because of the long indoor stabling period, the hay harvest determines the level of cattle stocking. Outer meadows (engi) and rough pasture near the farmstead (heimahagar) are losing importance, while the high pastures (afrettir) traditionally serve as extensive summer grazing for sheep and horse. Despite breeding progress, climatic instability still causes fluctuations in potato growing and in sporadic grain cultivation. The proportion of cattle to total animal stocking is taken as a measure of regional farm structure differentiation. The production and supply areas of the most important dairies are described and the final discussion considers possibilities of agricultural development within the framework of the economy.